SOLAR POWER PLANT (PLTS) PLANNING BASED ON PVSYST SOFTWARE IN THE JOINT LECTURE BUILDING "“ B TANJUNGPURA UNIVERSITY - Sanjaya, Willie; Yandri, Yandri; Hiendro, Ayong (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2024)
Renewable energy can be utilized as the main alternative to meet the soaring supply of electrical energy due to the increasing need for electrical energy in Indonesia every year, this research evaluates the solar power plant (PLTS) located in the Tanjungpura University Joint Lecture Building -B, Southeast Pontianak sub-district, Pontianak City. Based on the results of the calculation, the estimated daily energy demand of the Joint Lecture Building - B Tanjungpura University is 115.164 kWh / day and 48,651 kWh / year, the power calculated manually with an area of 156 m^2 solar modules produces a power of 31.2 kWp and the power from the simulation results of PVsyts software with an area of 195m^2 solar modules produces a power of 36 kWp. In this plan, the number of batteries produced by manual calculation is 252 and those produced in the simulation are 240 batteries. From the results of the economic analysis in this study, the total NPV of Rp. 594,737,202 LCC of Rp. 809,481,423 for levelized COE of Rp.1,507/kWh for operating costs or operating costs of Rp. 7,178,000, is the result of economic analysis for 25 years obtained from the results of the PVsyst software simulation.